Paradigms on Technology Development for Security Practitioners - Gkotsis, Ilias; Kavallieros, Dimitrios; Stoianov, Nikolai; Vrochidis, Stefanos; Diagourtas, Dimitrios; Akhgar, Babak; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book is authored by a rich mix of contributors from across the landscape of research, academia, LEAs, civil protection, and other first responders, practitioners, public and private organizations and industry to address some of the most contemporary challenges within global security domain. The authors cover topics such as protection of critical infrastructures (CI), serious and organized crime, counter (cyber) terrorism, border management, cybercrime, cybersecurity, management of disasters and crises, big data analytics, the application of AI and the legal and ethical dimensions of the implementation of cutting-edge technologies. The book benefits from research actions and lessons learned from more than 35 EU R&D projects within the security domain. The book not only addresses theoretical narratives pertinent to the subject but also identifies current challenges and emerging security threats, provides analysis of operational capability gaps, real world applied solutions, methodologies, and case studies within security domain. This is an open access book. Presents security practitioner driven technologies from practical, theoretical and legal/ethical point of view Offers R&D perspectives on strengthening security potential based on input from multidisciplinary stakeholders Addresses security topics from LEAs, Civil Protection authorities, first responders, cyber-security organizations, Critical Infrastructure operators and other stakeholders involved in societal resilience This book is open access, which means that you have free and unlimited access.
Introduction -- Part 1: Cyber Crime, Cyber Terrorism and Cyber Security -- Cybercrime and terrorism -- Cyber Security -- AI and Cyber -- Part 2: Effective management and security of EU external borders -- Border Security Technologies -- Methodological approaches to border security -- Integrated platforms for border security management -- Part 3 Serious and Organized Crime (SOC) -- Multimodal Data Fusion for combating SOC -- Big Data Processing and Analytics in context of SOC -- Data Visualisation and Decision Support -- Artificial Intelligence for combating SOC -- Part 4: Critical Infrastructures (CI) Resilience and Public Space Protection -- Cyber and System security for protection of CI -- Physical security of CI -- Case studies in protection of CI -- Protection of Public Spaces -- Part 5: Civil Protection and Disaster-Resilient Societies -- Crisis management -- Disaster management and Resilience strengthening technologies -- First responders technology -- Part 6: Strengthened Security Research and Innovation -- Part 7: Enhancing the defense capabilities of the EU -- Conclusion.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Security systems; Data protection; Computational intelligence; Security Science and Technology; Data and Information Security; Computational Intelligence